Assessment of Quality of Life in Patients with Double-J Ureteral Stents – A Questionnaire-Based Study - Hobot, Jakub (Quality in Sport, 2026)
Double-J (DJ) ureteral stents are widely used in modern urology to ensure effective drainage of the upper urinary tract in conditions such as urolithiasis, ureteral obstruction, malignancies, and postoperative management. Despite their clinical benefits, they are often associated with symptoms that impair patients’ quality of life. The aim of this study was to evaluate the impact of DJ ureteral stents on quality of life in patients treated at the Department of Urology, University Clinical Hospital in Opole, focusing on urinary symptoms, pain, daily functioning, and treatment effectiveness. The study included 200 patients with indwelling DJ stents. Data were collected using a proprietary questionnaire assessing demographics, indications, stent duration, symptoms, quality of life, and pharmacotherapy. Descriptive statistics were used. Lower urinary tract symptoms were common, especially nocturia (72%), urgency (68%), and incomplete emptying (61%). Pain was reported by many patients, including lower abdominal (55%) and lumbar pain. Overall, 74% reported reduced quality of life, affecting sleep, work, and sexual activity. Pharmacological treatment was used by 57%, mainly alpha-blockers and anticholinergics; 62% reported improvement, though full relief was rare. Longer stent duration was associated with greater symptom severity. DJ stents significantly impair quality of life due to frequent symptoms and pain. Pharmacological treatment provides partial relief. Minimizing stent duration and individualized management may reduce morbidity.